Features of pricing in the field of telecommunications of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
"Upon reviewing some aspects of pricing in the telecommunications sector in the article, authors have attempted to show the steps that the operator carries in the formation of prices for the service, the steps in establishing a new tariff structure, some theoretical functions of the tariff, and JSC “Kazakhtelecom’s” tariff policy’s basic principles. The idea of the need in developing and implementing new informational business models had been offered. "
Keywords: "pricing; telecommunication "